Pemetaan Kejadian Stunting Dengan Perilaku Stop Buang Air Besar Sembarangan Per Kabupaten/Kota Di Provinsi Nusa Tenggara Timur Tahun 2021 - Artha Prabawa; Dwita Maulida (Politeknik Negeri Jember, 2023)
Stunting in toddlers occurs because of long-term malnutrition, which has the potential to cause recurrent infections and chronic malnutrition. Contributing factors include a poor nutritious diet and poor sanitation, including open defecation, which can contaminate the environment with human feces and increase the risk of spreading diarrhea-causing bacteria to children. The province of NTT is one of those with a high prevalence of stunting in Indonesia. This study aims to determine the distribution of stunting in NTT and its association with the status of villages/kelurahan in NTT where open defecation is still practiced. The research was conducted using a Geographic Information System (GIS) application using classification, scoring, and overlay techniques. The result is that there are seven districts that are prioritized for tackling stunting with interventions on community behavior to stop open defecation. These districts include Rote Ndao, West Sumba, Southwest Sumba, Central Sumba, Kupang, North Central Timor, and Malacca.